Cellulose nanocrystals and cellulose nanofibrils based hydrogels for biomedical applications - Du, Haishun; Liu, Wei; Zhang, Miaomiao; Si, Chuanling; Zhang, Xinyu; Li, Bin (Carbohydrate polymers, 2019)
•Preparation of CNCs and CNFs was briefly introduced.•Fabrication of CNCs and CNFs based hydrogels was elaborated.•Emerging methods such as 3D printing were highlighted.•Biomedical applications of CNCs and CNFs based hydrogels were summarized.•Prospects and challenges of CNCs and CNFs based hydrogels were discussed. The production of cellulose nanomaterials from lignocellulosic biomass opens an opportunity for the development and application of new materials in nanotechnology. Over the last decade, cellulose nanomaterials based hydrogels have emerged as promising materials in the field of biomedical applications due to their low toxicity, biocompatibility, biodegradability, as well as excellent mechanical stability. In this review, recent progress on the preparation of cellulose nanocrystals (CNCs) and cellulose nanofibrils (CNFs) based hydrogels and their biomedical applications is summarized and discussed based on the analyses of the latest studies (especially for the reports in the past five years). We begin with a brief introduction of the differences in preparation methods and properties of two main types of cellulose nanomaterials: CNCs and CNFs isolated from lignocellulosic biomass. Then, various processes for the fabrication of CNCs based hydrogels and CNFs based hydrogels were elaborated, respectively, with the focus on some new methods (e.g. 3D printing). Furthermore, a number of biomedical applications of CNCs and CNFs based hydrogels, including drug delivery, wound dressings and tissue engineering scaffolds were highlighted. Finally, the prospects and ongoing challenges of CNCs and CNFs based hydrogels for biomedical applications were summarized. This work demonstrated that the CNCs and CNFs based hydrogels have great promise in a wide range of biomedical applications in the future.